2005
DOI: 10.2355/isijinternational.45.1187
|View full text |Cite
|
Sign up to set email alerts
|

The Coupled Model of a Microstructure Evolution and a Flow Stress Based on the Dislocation Theory

Abstract: A coupled mathematical model has been developed that predicts a microstructure evolution and a flow stress during and after the process of deformation. A part of the model, which is responsible for the microstructure evolution, consists of models of a recrystallization and a grain growth. A dynamic, static and metadynamic recrystallization is considered as a whole. The flow stress is calculated on the basis of the dislocation theory. Changes of the dislocation density during the deformation are described by mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Different models and methods were implemented into different FEM codes for confirmation of their effectiveness. Internal variables models are represented by the original model [16] and by the modified state variables model, which receives properties of IVM with introduction of the three internal variables [14]. State variables models (SVM) are represented by the Sellars-Davenport model, table method with nonlinear interpolation and others.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different models and methods were implemented into different FEM codes for confirmation of their effectiveness. Internal variables models are represented by the original model [16] and by the modified state variables model, which receives properties of IVM with introduction of the three internal variables [14]. State variables models (SVM) are represented by the Sellars-Davenport model, table method with nonlinear interpolation and others.…”
Section: Discussionmentioning
confidence: 99%
“…But it is calculated in the way proposed by Svyetlichnyy [14]. Four differential state equations are used for the extended volume V ex calculations.…”
Section: Internal Variable Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The models of the dislocation density, nucleation and growth of recrystallized grains are described in detail elsewhere. 22,23) Here, they are presented shortly. The following model of the dislocation density is applied for all grains.…”
Section: Recrystallizationmentioning
confidence: 99%
“…and after deformation, however, limited studies have been reported on the microstructural evolution in terms of recrystallized volume fraction and grain size. A large group of these models are based on the Johnson-Mehl-Avrami-Kolmogorov (JMAK) equation approach [15][16][17][18][19][20][21]. However, the ideal JMAK behavior is rarely exhibited by real materials.…”
Section: Introductionmentioning
confidence: 99%